2005
DOI: 10.1242/jcs.02503
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitously expressed secretory carrier membrane proteins (SCAMPs) 1-4 mark different pathways and exhibit limited constitutive trafficking to and from the cell surface

Abstract: Secretory carrier membrane proteins (SCAMPs) 1-4 are ubiquitously expressed and are major components of the eukaryotic cell surface recycling system. We investigated whether different SCAMPs function along distinct pathways and whether they behave like itinerant cargoes or less mobile trafficking machinery. In NRK cells, we show by immunofluorescence microscopy that different SCAMPs are concentrated mostly adjacent to one another in the trans-Golgi network and endosomal recycling compartment. By immunoelectron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 43 publications
8
61
0
Order By: Relevance
“…In these cells, as well as in HEK-293 cells, SERT and SCAMP2 staining neither overlaps significantly with TfR-positive endosomes, nor with the Golgi marker TGN38. Our data are in general agreement with a recent study by Castle and Castle, in which SCAMP2 showed limited co-localization with TGN38 and only partial co-localization with TfR in NRK cells (26). SCAMPs are predominantly associated with recycling rather than degradation pathways, suggesting that through the interaction with SCAMP2, SERT might be targeted to a distinct recycling compartment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In these cells, as well as in HEK-293 cells, SERT and SCAMP2 staining neither overlaps significantly with TfR-positive endosomes, nor with the Golgi marker TGN38. Our data are in general agreement with a recent study by Castle and Castle, in which SCAMP2 showed limited co-localization with TGN38 and only partial co-localization with TfR in NRK cells (26). SCAMPs are predominantly associated with recycling rather than degradation pathways, suggesting that through the interaction with SCAMP2, SERT might be targeted to a distinct recycling compartment.…”
Section: Discussionsupporting
confidence: 93%
“…SCAMP2 belongs to a family of proteins that are major components of the eukaryotic cell surface recycling system. SCAMPs are ubiquitously expressed and are found on secretory organelles involved in regulated exocytosis, on recycling vesicles that shuttle to and from the plasma membrane and also on synaptic vesicles (18,19,26,30). SCAMP2 directly interacts with SERT both in a heterologous expression system and in rat brain tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCAMPS are found in both the TGN and the endosomal recycling compartment in NRK cells, and they appear to be concentrated within the motile population of early and recycling endosomes . Thus, SCAMPs appear to be reliable indicators for postGolgi endocytic and exocytic trafficking in animal cells (FernandezChacon and Sudhof, 2000;Castle and Castle, 2005;Liu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…SCAMPs are found in multiple organelles such as the Golgi apparatus, trans-Golgi network, recycling endosomes, synaptic vesicles, and the plasma membrane (33,34) and have been shown to play a role in exocytosis (35)(36)(37)(38) and endocytosis (39). Currently, five isoforms of SCAMP have been identified in mammals.…”
mentioning
confidence: 99%